(untitled) (Journal of Economic Research & Business Administration, 2015)
The paper assessed the extent to which the socio-economic conditions of the pace of forced industrialinnovative economic development of Kazakhstan. Also determined by how consistent these conditions the requirements generated by the authors: stability , dynamics , competitiveness , adequacy and effectiveness.The authors investigated the dynamics of macroeconomic indicators of the national economy in 2008-2012: GDP growth and its structure, the volume indices of industrial and agricultural production , foreign trade , employment, unemployment and wages, etc. It was found that signifi cant funds aimed at the modernization of the national economy within the framework of SPFIID did not have undue infl uence on its diversifi cation also analyzed SPFIID execution targets , causing severe negative discrepancies found between the planned indicators for the state program and its actual implementation . Identifi ed obstacles in the implementation of the Program of forced industrial-innovative development .